Early Growth Response of Mint Cuttings (Mentha spicata) Growth in Soil and Water Rooting Media - Andina Dwiana Marsa; Cheryska Alinza; Nisma Hariyanti Ritonga; Hesti Riany (ORGANISMS: JOURNAL OF BIOSCIENCES, 2026)
The study aims to evaluate the early growth response of mint cuttings (Mentha spicata) to two rooting media: water and soil. The study was conducted at the Biology Laboratory of the Faculty of Science and Technology, UIN Sulthan Thaha Saifuddin Jambi, with a 7-day observation period. The parameters observed included the percentage of cuttings that survived, time to the first leaf, number of leaves, and number of roots. The results showed that mint cuttings in a water medium had better initial growth than those in a soil medium. The average number of roots in water medium was 22.00 ± 15.56, while the average number of leaves in water medium reached 13.50 ± 7.78. The first leaves appeared earlier in the water medium (on the third day). The survival rate of cuttings in both media reached 100%. Thus, water medium can be recommended as a more optimal initial rooting medium for mint cutting propagation before being transferred to a subsequent planting medium.